Inpatient burden and mortality of heatstroke in the United States - Wisit Kaewput (2022)
Background: This study aimed to assess inpatient prevalence, characteristics, outcomes, and resource utilisation of hospitalisation for heatstroke in the United States. Additionally, this study aimed to explore factors associated with in-hospital mortalities of heatstroke. Methods: The 2003-2014 National Inpatient Sample database was used to identify hospitalised patients with a principal diagnosis of heatstroke. The inpatient prevalence, clinical characteristics, in-hospital treatments, outcomes, length of hospital stay, and hospitalisation cost were studied. Multivariable logistic regression was performed to identify independent factors associated with in-hospital mortality. Results: A total of 3372 patients were primarily admitted for heatstroke, accounting for an overall inpatient prevalence of heatstroke amongst hospitalised patients of 36.3 cases per 1 000 000 admissions in the United States with an increasing trend during the study period (P <.001). Age 40-59 was the most prevalent age group. During the hospital stay, 20% required mechanical ventilation, and 2% received renal replacement therapy. Rhabdomyolysis was the most common complication. Renal failure was the most common end-organ failure, followed by neurological, respiratory, metabolic, hematologic, circulatory, and liver systems. The in-hospital mortality rate of heatstroke hospitalisation was 5% with a decreasing trend during the study period (P <.001). The presence of end-organ failure was associated with increased in-hospital mortality, whereas more recent years of hospitalisation was associated with decreased in-hospital mortality. The median length of hospital stay was 2 days. The median hospitalisation cost was $17 372. Conclusion: The inpatient prevalence of heatstroke in the United States increased, while the in-hospital mortality of heatstroke decreased.